2017
DOI: 10.1090/mcom/3248
|View full text |Cite
|
Sign up to set email alerts
|

Orders of Tate-Shafarevich groups for the Neumann-Setzer type elliptic curves

Abstract: We present the results of our search for the orders of Tate-Shafarevich groups for the Neumann-Setzer type elliptic curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Park, Poonen, Voight and Wood [15] have formulated an analogous (but less precise) conjecture for the family of all elliptic curves over the rationals, ordered by height. Note similarity with the predictions by Delaunay [8] for the case of quadratic twists of a given elliptic curve (and numerical evidences in [5] [7]), and with a variant of this phenomenon in the case of the family of Neumann-Setzer type elliptic curves [6].…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Park, Poonen, Voight and Wood [15] have formulated an analogous (but less precise) conjecture for the family of all elliptic curves over the rationals, ordered by height. Note similarity with the predictions by Delaunay [8] for the case of quadratic twists of a given elliptic curve (and numerical evidences in [5] [7]), and with a variant of this phenomenon in the case of the family of Neumann-Setzer type elliptic curves [6].…”
Section: Introductionsupporting
confidence: 79%
“…It turns out that in a case of rank zero quadratic twists E d of a fixed elliptic curve E the values of log(|X(E d )|/ √ d) are the natural ones to consider (compare the numerical experiments in [5], [7]). We also have good conjecture for a family of rank zero Neumann-Setzer type elliptic curves [6].…”
Section: Distributions Of |X(e M )|mentioning
confidence: 89%
See 1 more Smart Citation
“…Very recently, Bhargava, Skinner and Zhang [1] proved that at least 66.48% of all elliptic curves over Q, when ordered by height, satisfy the weak form of the Birch and Swinnerton-Dyer conjecture, and have finite Tate-Shafarevich group.When E has complex multiplication by the ring of integers of an imaginary quadratic field K and L(E, 1) is non-zero, the p-part of the Birch and Swinnerton-Dyer conjecture has been established by Rubin [27] for all primes p which do not divide the order of the group of roots of unity of K. Coates et al [5] [4], and Gonzalez-Avilés [17] showed that there is a large class of explicit quadratic twists of X 0 (49) whose complex L-series does not vanish at s = 1, and for which the full Birch and Swinnerton-Dyer conjecture is valid (covering the case p = 2 when K = Q( √ −7)). The deep results by Skinner-Urban ([29], Theorem 2) (see also Theorem 7 in section 8.4 below) allow, in specific cases (still assuming L(E, 1) is non-zero), to establish p-part of the Birch and Swinnerton-Dyer conjecture for elliptic curves without complex multiplication for all odd primes p (see examples in section 8.4 below, and section 3 in [10]). The numerical studies and conjectures by Conrey-Keating-Rubinstein-Snaith [7], Delaunay [12][13], Watkins [31], Radziwi l l-Soundararajan [25] (see also the papers [11][10] [9], and references therein) substantially extend the systematic tables given by Cremona.This paper continues the authors previous investigations concerning orders of Tate-Shafarevich groups in quadratic twists of the curve X 0 (49).…”
mentioning
confidence: 99%
“…In earlier papers (see [11], [7], [8], [9], [10]), we have investigated some numerical examples of E defined over Q for which L(E, 1) is non-zero and the order of Ш(E) is large.…”
mentioning
confidence: 99%